PENENTUAN KADAR ASAM LEMAK BEBAS DALAM PRODUK RBD OLEIN DAN RBD STEARIN PADA PROSES FRAKSINASI - Sari, Risma; Azahra, Fauziah (Politeknik ATI Padang, 2017)
Palm oil is producer a vegetable oil can be relied upon, because the resulting oil has various superiority compared with oil resulting by other plants. Palm oil quality is determined of some parameter among other is a free fatty acid. Measuring a free fatty acid (FFA) determined by using a method alkalimetri. RBD Stearin is a faction solid fat which come from RBDPO (Refined Bleached and Deodorized Oil) who has experienced refined complete.this stearin is white and has a smell like the smell of oil. RBD Olein is a faction liquid fat which come from RBDPO (Refined Bleached and Deodorized Palm Oil) who has experienced refined, olein is also be called with cooking oil which has a golden yellow color. Of the analysis result is a available a free fatty acid degrees RBD Olein 0.0771 % and RBD Stearin 0.0775 % of the analysis results is available have met the spec PORAM.